Pre-Service Teachers’ Perception on the Use of Online Learning at English Education Department of Universitas Muhammadiyah Yogyakarta - Sanda Aginza Hadi Pradita (PBI 15 UMY 038, 2015)
*38 Online Learning has been implemented in almost all universities. However, not all students at English Education Department of Universitas Muhammadiyah Yogyakarta who are as pre-service teachers are familiar with the use of online learning since the implementation of online learning in this department has not got an equal portion compared with the face to face learning. This study aimed at finding out these pre-service teachers on the use of online learning at EED of UMY. This study used qualitative research design and specifically employed descriptive qualitative research. The researcher chose interview as the instrument to gather the data. There were six (6) participants coming from pre-service teachers of EED of UMY from batch 2011. Participants were chosen based on some criteria. They were students who were highly involved participating in online learning, had good technological capability and they had already enrolled in all courses which implemented online learning. In analyzing the data, the researcher used three kinds of coding including open coding, axial coding, and also selective coding to get final categorization of the data. Prior to it, the researcher had already done member checking to get validity of the data before analyzing the data. The first finding of this study showed that there were two main interactions which were taken place in the online learning context at EED of UMY. The interactions perceived by the participants were student-student vii interaction and student-teacher interaction. The second finding is about the activities occurred in online learning at EED of UMY. There were five activities used by the lecturers in the online learning context which were discussion, feedback from the lecturer, feedback from friends, answer-question session, and commenting. The third purpose of this study is finding out the pre-service teachers’ perception on the use of online learning toward their language skill. Based on finding from interview, it was revealed that by having online learning, students pay more attention to structure, and the use of language become more formal. Online learning also enhances pre-service teachers’ writing skill, reading skill, vocabulary, grammar, and language development. The fourth finding is related to pre-service teachers’ preferences dealing with their experiences in online learning. The finding showed that Edmodo and WordPress became the tools which are mostly prefered by the participants. The last finding on this study discussed the strengths and the weaknesses of online learning. The finding revealed the strengths of online learning including flexibility, providing updated material and information, encouraging reading, personal development, and enriching learning resources. On the other hand, the weaknesses of online learning included decreasing of social relationship, decreasing oral communication, spending cost for the equipment, lack of internet connection, lack of an actual teachers’ feedback, and lack of technological skill.